2021
DOI: 10.1038/s41419-021-03526-w
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in inflammasome signaling by the chronic Pseudomonas aeruginosa isolates from cystic fibrosis patients results in an increase in inflammatory response

Abstract: Pseudomonas aeruginosa is a common respiratory pathogen in cystic fibrosis (CF) patients which undergoes adaptations during chronic infection towards reduced virulence, which can facilitate bacterial evasion of killing by host cells. However, inflammatory cytokines are often found to be elevated in CF patients, and it is unknown how chronic P. aeruginosa infection can be paradoxically associated with both diminished virulence in vitro and increased inflammation and disease progression. Thus, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…However, IL-6 levels in the sputum of patients with advanced CF lung disease was extremely low but normal systemic IL-6 production was found [ 44 ]. Another study found that early isolate of P. aeruginosa from the respiratory system of CF patients could induce the expression of IL-1β but minimal expression of TNF, IL-6 and IL-8; while inversely, chronic isolates could induce higher expression of TNF, IL-6 and IL-8 and low IL-1β production [ 47 ]. Moreover, measurement of circulating and sputum cytokines from CF patients with chronic P. aeruginosa infection revealed that higher levels of IL-1 receptor antagonist (IRAP), IL-lα, IL-1β, IL-6 and TNF-α could be detected from sputum, while very little circulating cytokines were detected [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-6 levels in the sputum of patients with advanced CF lung disease was extremely low but normal systemic IL-6 production was found [ 44 ]. Another study found that early isolate of P. aeruginosa from the respiratory system of CF patients could induce the expression of IL-1β but minimal expression of TNF, IL-6 and IL-8; while inversely, chronic isolates could induce higher expression of TNF, IL-6 and IL-8 and low IL-1β production [ 47 ]. Moreover, measurement of circulating and sputum cytokines from CF patients with chronic P. aeruginosa infection revealed that higher levels of IL-1 receptor antagonist (IRAP), IL-lα, IL-1β, IL-6 and TNF-α could be detected from sputum, while very little circulating cytokines were detected [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies of P. aeruginosa pathogenesis in model systems have used laboratory strains, such as PA14, PAO1 and PAK, which are well characterized and fully sequenced. However, pathogenesis studies using clinical isolates illustrate the very substantial differences between these laboratory organisms that reflect properties of environmental strains of P. aeruginosa or those taken from the blood stream, versus the organisms that have undergone adaptive changes to long term survival in the human airway [9,21,41,54,55]. Similar discrepancies are observed in the media used to mimic the host airway for in vitro P. aeruginosa studies, especially in CF; artificial media containing DNA and mucin reflect many of the conditions expected in the airway but fail to include the major immune cell metabolites, succinate and itaconate or provide ROS that are an inherent component in vivo conditions [56][57][58][59].…”
Section: Model Systems In Cf and P Aeruginosa Pneumoniamentioning
confidence: 99%
“…THP-1 human monocyte/macrophage cell lines activated by P. aeruginosa lipopolysaccharide (LPS) or by P. aeruginosa itself are a suitable model for examining the effects of new therapeutic agents on the immune response [ 17 , 18 , 19 ]. P. aeruginosa LPS acts by binding to the Toll-like receptors (TLRs) on the cellular surface and activates the nuclear factor-κB (NFκB) signaling pathway responsible for the regulation of the transcription of pro-inflammatory cytokines (e.g., IL-6, IL-8, or TNF-α) [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%